PENGENALAN STRATEGI PEMASARAN PADA PRODUK DAUR ULANG DI PAMULANG TANGERANG SELATAN - Rodhiah; Wijaya , Yefta Leonardi Agusta; Bakti , Kevin Karunia (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
This activity aims to help business owners introduce marketing strategies to recycling businesses in the Pamulang area of South Tangerang which are made from used plasik bottles large and small, then processed into handicraft products such as lamp stamps, aquariums, flower pots and others. This activity was inspired by the problem of partners in terms of marketing recycled products that have been processed. Based on preliminary observations to partners made by coming directly to the owner, the main problem lies in the marketing aspect. This is due to the weak knowledge of partners about marketing strategies. So that the recycled products that have been successfully made cannot be marketed to the maximum, only around the business location. The method offered in this activity is training / socialization on online marketing strategies through Zoom meetings. The results of the activity show that the activity has been carried out properly and runs smoothly, problems that arise in partners can be resolved. So that partners are able to understand about marketing strategies, this is evidenced by the results of evaluating partner answers 100% understanding of the material that has been submitted by the PKM Team leader.